Benthic communities in the Southwest Atlantic Ocean: Conservation value of animal forests at the Burdwood Bank slope. Issue 3 (27th January 2020) - Schejter, Laura; Genzano, Gabriel; Gaitán, Esteban; Perez, Carlos D.; Bremec, Claudia S.
Abstract: The characterization of benthic communities at the Burdwood Bank slope (≥200 m depth) is provided, comprising data from the marine protected area (MPA) Namuncurá II (created in December 2018), as well as from some deep bathyal surrounding areas in the Southwest Atlantic Ocean. This information was acquired during two research cruises with RV Puerto Deseado (Argentina) during 2016 and 2017. Marine animal forests were detected in the study area: coral gardens, mainly composed of alcyonaceans, were detected in the south and west of Burdwood Bank (MPA Namuncurá II) and neighbouring areas, whereas pennatulacean aggregations were detected in the north‐west of the plateau. The three‐dimensional structures of live but also dead corals provide substrate and refuge to many associated species. Benthic communities dominated by sponges were also recorded between 200 and 300 m in depth. Six sites that meet the characteristics of vulnerable marine ecosystems (VMEs) are reported. Conservation strategies applied to scarcely known austral Argentinean waters led to the establishment of a pioneer MPA (Namuncurá I). Following the management plan that aimed to establish the biodiversity of Namuncurá I and neighbouring areas, the area of protection has now been enlarged to include the southern slope of the bank (currently Namuncurá II), where marine animal forests were detected, at depths below 200 m. The data presented here provide empirical evidence to support the conservation value of the region.